EVALUATION OF THE STAFF DEVELOPMENT PROGRAM AMONG HIGH SCHOOL TEACHERS IN BANDA ACEH - siti safura (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2016)
This paper aimed at examining the impact of staff development program on teaching performance. The questionnaire was administered to 100 high school teachers in Banda Aceh, Indonesia. Descriptive analysis was utilized in this study. This study found that the majority of high school teachers in Banda Aceh perceived that the staff development program has impact on teaching performance. Meanwhile, in terms of genders, duration and the areas focused on this program, this study found inconclusive results regarding the impact of the staff development program. In terms of gender, it was indicated that each respondent had contrasting views on the impact of the staff development program. Two variables of teaching performance indicated no significant difference among teachers. However, four variables revealed significant difference among teachers. With regards to the duration of staff development program attended, each respondent also had different views on the impact of staff development program. Four variables of teaching performance indicated no significant difference among teachers, while, two variables indicated the significant difference among teachers. Regarding the most areas which are focused on staff development program, it was found that there was no significant difference among teachers in perceiving the impact of staff development program.